50 weeks of STEM labs : 250 experiments for 50 weeks of STEM-tastic fun! - Frinkle, Andrew, ....- (S.l. : 50STEMLabs.com, 2015)
50 Weeks of STEM Labs is a set of weekly plans focusing on a theme, such as a type of project or a specific material. Each week features 5 quick projects to do with that theme. This is enough projects for a whole school year and more! You can even spend more time on projects that require more learning and exploration. Included are 250 STEM projects in 50 fun themes. Each theme is based on a concept or material to be used, like: *Pasta Noodles, Tape, Glue, Cups, Paperclips, or Eggs *Recycling Projects, Airplanes, or Musical Instruments